Pengaruh Pengembangan Karir Dan Promosi Jabatan Terhadap Semangat Kerja Karyawan ( Studi Kasus PT Indomarco Prismatama Cabang Malang ) - Wahyu Irawan; Achmad Agus Priyono; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This research examines to analyze the effect of career development and job promotion on employee morale (Case Study of PT Indomarco Prismatama Malang Branch). The sample in this study were 60 employees who were used as respondents, the method used in this study was multiple linear regression with primary data to be analyzed using the SPSS For Windows application. Based on the results of research and discussion in the previous chapter, it is concluded that the simultaneous test results show that career development and job promotion variables have an effect on employee morale. The partial test results variable career development and job promotion have a positive effect on employee morale. Keywords: Career Development, Job Promotion, Work Spirit